Media Agenda-setting and Framing in the Construction of Public Discourse - Boluwatife Ayobami Araba (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
This paper analyzes the roles that Agenda-setting and Framing theories play in influencing public perception and interpretation of social and political issues through the lens of mass media. Agenda-setting Theory describes the ability the news media has to shape the public agenda by creating a certain opinion or interpretation, which suggests that the media can shape public priorities and interpretation by determining which issues receive greater attention and prominence in news coverage. By consistently highlighting certain topics, the media increase their perceived importance among audiences. Framing theory further explains how a presentation (or frame) of information influences how the audience interprets and makes decisions about it, focusing on how something is said rather than just what is said, by emphasizing certain aspects, simplifying messages, and adding meaning to shape the public action and perception, especially the media, politics and government. Using theoretical analysis and relevant literature, this study explores how both theories complement each other in explaining media influence on public discourse. The paper argues that the media may not only direct public attention toward particular issues but also shape the opinions and interpretation attached to them, thereby playing a crucial role in the formation of public opinion and societal narratives.